The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Squamous Cell Carcinoma - Hallmark and Treatment Modalities 2020
DOI: 10.5772/intechopen.85650
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Oral Squamous Cell Carcinoma

Abstract: Oral carcinogenesis is a molecular and histological multistage process featuring genetic and phenotypic molecular markers which involves enhanced function of several protooncogenes, oncogenes and/or the deactivation of tumor suppressor genes, resulting in the over activity of growth factors and its cell surface receptors, which could enhance messenger signaling intracellularly, and/or leads to the increased production of transcription factors. Alone oncogenes are not responsible for carcinogenesis, genes havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…7 This tumor is initiated by the process of squamous metaplasia and dysplasia that occurs in the bronchial epithelium. 24 Consists of squamous cells with…”
Section: Resultsmentioning
confidence: 99%
“…7 This tumor is initiated by the process of squamous metaplasia and dysplasia that occurs in the bronchial epithelium. 24 Consists of squamous cells with…”
Section: Resultsmentioning
confidence: 99%
“…For example, cervical cancer diagnosis requires the uncomfortable procedure of collecting cells from the cervix, the lower and narrow end of the uterus located at the top of the vagina. This method called a “Pap smear” can pose physical discomfort and hinder the early detection and the subsequent treatment of cervical cancer. , Cervical cancer is characterized by the growth of abnormal cells in the cervical lining, with squamous cell carcinoma being the most prevalent type . In its initial stages, cervical cancer might not have noticeable symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…About 90% of all oral cancers are OSCCs (1). Oral cancers that affect the salivary glands, pharynx, and oral cavity account for 2% to 4% of all cancer cases globally (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous single or multicenter studies have consistently shown a relationship between a number of prognostic markers and disease-specific survival, local and regional recurrence, and lymph node metastasis. The prognosticators are extranodal extension (ENE), lymphovascular invasion (LVI), perineural invasion (PNI), depth of invasion (DOI), and pattern of invasion (POI) (1,3,5) .…”
Section: Introductionmentioning
confidence: 99%